Challenges And Barriers Of Blended Learning Among Asian Health Sciences Students: A Pilot Study - Huda Saber; Rosliza Abdul Manaf; Anna Tasnim Basman; Lee Ping Yein; Rosemaliza Kamalludeen; Rosni Ibrahim; Syafinaz Amin-Nordin; Suhaila Sanip (Penerbit Universiti Sains Malaysia and Malaysian Association of Education in Medicine and Health Sciences (MAEMHS), 2024)
Indexed by Scopus/MyCite